Conflict of interests or transparency at the World Health Organization? An analysis of the Framework of Engagement with non-State actors and the Member States\' positions during the negotiations process (2012-2016) - Fedatto, Maíra da Silva (2020)
Underfunded and overburdened, the World Health Organisation has been unable to respond swiftly and effectively to existing and conceivable global health challenges. It became perceptible after the slow and highly criticised response to the Ebola outbreak in West Africa, in 2014. Currently, while the WHO has been facing a financial crisis, the growing participation of several non-State actors such as non-governmental organisations, pharmaceutical companies, transnational organisations, philanthropic foundations and others has led to a weakening of the Organisation\'s leadership. The involvement of these \'new\' actors can undoubtedly bring institutional, technical, political and financial resources not only to global public health but also to support the WHO in accomplishing its guiding and coordinating role. However, the rise of several non-State actors also creates challenges for coordination and raises questions about the roles these organisations should play, the rules by which they play, and who should set those rules. Considering the intense relationship of the WHO with a vast number of non-State actors, Member States have historically been trying to establish a policy to regulate these relations. In 2012, the Framework of Engagement with non-State Actors (FENSA) was presented with the main goal of regulating the relation of the WHO with non-governmental organisations, the private sector, philanthropic foundations and academic institutions. By investigating the negotiation process through document analysis and interviews, I seek to identify the positions of the most active Member States during the negotiation of the Framework and to understand the different coalitions that were designed. I would also take in to account the perspective of the non-State actors embraced by FENSA and pertaining to the WHO itself. By disclosing FENSA, specifically its context and the negotiation process, the ongoing powerful influence of some non-State actors on global health governance, and consequently at the WHO, becomes easier to understand.